Organizational culture and environmental performance of manufacturing - Magsi, Hussain Bakhsh; Tze, San Ong; Jo, Ann Ho; Sheikh Hassan, Ahmad Fahmi (M D P I AG, 2018)
Because it has become more and more urgent for organizations to implement environmental strategies with the support of organizational culture, this study considers it necessary to conduct an empirical study to examine the impact of organizational culture on environmental performance. Synthesizing the perspectives of organizational culture and environmental performance, we applied a theoretical model in the manufacturing industry of Pakistan linking an organizational culture that supports environmental practices for better environmental performance. Based on a survey of 314 manufacturing firms, using Smart-PLS, the current study found that adaptability, mission and consistency positively affect environmental performance. However, involvement does not have an effect on environmental performance. Additionally, organizational culture as a latent variable has a strong impact on environmental performance. The study is one of the first, to the author’s knowledge that links OC and EP in a developing economy, in this case Pakistan.